A Job-Shop Scheduling Task for Evaluating Coordination during Computer Supported Collaborative Work - Tan, Desney; Gergle, Darren; Czerwinski, Mary (2005)
Researchers have begun to explore tools that allow multiple users to collaborate across multiple devices. One class of these tools allows users to simultaneously place and interact with information on shared displays. Unfortunately, there is a lack of good tasks to evaluate the effectiveness of these tools for information coordination in such scenarios. In this paper, we present collaborative job-shop scheduling, a task we have designed to evaluate systems and interactions within computer supported collaboration environments. We describe properties that make the task useful, as well as evaluation measures that can be used with this task. We validate the feasibility of the task and demonstrate analysis techniques in an experiment we conducted to compare the differences between presenting information serially versus simultaneously on a large shared display. Results from this experiment show the benefits of shared visual information when performing coordination tasks.